KARAKTERISTIK PENDERITA PREEKLAMSIA DI RSUP PROF. Dr. R. D. KANDOU MANADO - Warouw, Patricia C.; Suparman, Erna; Wagey, Freddy W. (e-CliniC, 2016)
Abstract: Worldwide there are about 76,000 pregnant women die each year due to preeclampsia and other hypertensive disorders in pregnancy. The incidence rate of preeclampsia in the United States, Canada, and Western Europe ranges from 2-5%. In developing countries, the rate ranges from 4-18% of all pregnancies. In Indonesia, the Maternal Mortality Ratio (MMR) of the period of 2008 to 2012 was 359 deaths per 100,000 live births. The occurrence of preeclampsia in Indonesia is about 3-10% of all pregnancies. This study aimed to determine the characteristics of patients with preeclampsia. This was a retrospective descriptive study. Samples were pregnant women with preeclampsia and had complete medical records at Prof. Dr. R. D. Kandou Hospital during the period of January 1, 2014 until December 31, 2014. The results showed that the number of pregnant women with preeclampsia were 201 people. Mild preeclampsia and severe preeclampsia were most prevalent in the age group of 20-35 years (70% and 61.46%) meanwhile superimposed preeclampsia in the age group of >35 years (78.13%). Preeclampsia was mostly among multiparity. Superimposed preeclampsia was found in 32 cases. Most pregnant women with preeclampsia had a BMI ≥ 30.00. Conclusion: Most preeclampsia cases occured in the age group of 20-35 and> 35 years with multiparity, some had hypertension, and mostly were obese. Keywords: mild preeclampsia, severe preeclampsia, superimposed preeclampsia, age, parity, nutritional status (obesity). Abstrak: Diseluruh dunia sekitar 76.000 wanita hamil meninggal setiap tahun akibat preeklamsia dan gangguan hipertensi lainnya pada kehamilan. Insiden preeklamsia di Amerika Serikat, Kanada, dan Eropa Barat berkisar 2-5% sedangkan di negara berkembang berkisar 4-18% dari semua kehamilan. Di Indonesia Maternal Mortality Ratio (MMR) periode 2008 sampai 2012 sebesar 359 kematian per 100.000 kelahiran hidup. Frekuensi kejadian preeklamsia di Indonesia sekitar 3-10% dari semua jumlah kehamilan. Penelitian ini bertujuan untuk mengetahui karakteristik penderita preeklamsia. Jenis penelitian ini deskriptif retrospektif. Sampel penelitian ialah ibu hamil dengan preeklamsia dan mempunyai data rekam medis lengkap di RSUP Prof. Dr. R.D. Kandou periode 1 Januari 2014 sampai 31 Desember 2014. Hasil penelitian menunjukkan bahwa jumlah ibu hamil dengan preeklamsia 201 orang. PER dan PEB terbanyak ditemukan pada kelompok usia 20-35 tahun (70% dan 61,46%) sedangkan superimposed PE pada kelompok usia >35 tahun (78,13%). Preeklamsi terbanyak pada paritas multigravida. Superimposed PE berjumlah 32 kasus. Ibu hamil dengan preeklamsia terbanyak memiliki IMT ≥30.00. Simpulan: Preeklamsia terjadi pada kelompok usia 20-35 dan >35 tahun dengan paritas multipara, sebagian dengan riwayat hipertensi, dan sebagian besar disertai obesitas.Kata kunci: preeklamsia ringan, preeklamsia berat, superimposed preeklamsia, usia, paritas, status gizi (obesitas).